Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1001/archneur.1996.00550060093022
|View full text |Cite
|
Sign up to set email alerts
|

Regional Brain Tissue Composition in Children With Hydrocephalus

Abstract: Regional variations in brain tissue composition in children with shunted hydrocephalus correlate with a variety of cognitive and visuomotor functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 17 publications
3
42
0
Order By: Relevance
“…There were no differences between children with or without MMC, which indicates that the visuo-motor tests (Trail Making Test and Tower of London Test) also reflect deficits in planning and speed and not deficits in motor functions in children with MMC. Deficits in visual and visuo-spatial functions can be partly explained by the thinning of the posterior cortex, which is often found as a secondary CNS insult in children with hydrocephalus (Dennis et al, 1981, Fletcher et al, 1996. In spite of the fact that children with hydrocephalus have fluent spontaneous language in everyday life, they had difficulty performing the word-finding task in this study.…”
Section: The Impact Of Hydrocephalus On Cognition and Neuropsychologimentioning
confidence: 64%
See 4 more Smart Citations
“…There were no differences between children with or without MMC, which indicates that the visuo-motor tests (Trail Making Test and Tower of London Test) also reflect deficits in planning and speed and not deficits in motor functions in children with MMC. Deficits in visual and visuo-spatial functions can be partly explained by the thinning of the posterior cortex, which is often found as a secondary CNS insult in children with hydrocephalus (Dennis et al, 1981, Fletcher et al, 1996. In spite of the fact that children with hydrocephalus have fluent spontaneous language in everyday life, they had difficulty performing the word-finding task in this study.…”
Section: The Impact Of Hydrocephalus On Cognition and Neuropsychologimentioning
confidence: 64%
“…The few existing studies of executive function in children with hydrocephalus generally illustrate single, or just a few, aspects. Fletcher et al (1996) reported poorer results on planning tasks performed by children with hydrocephalus, but they were not discussed in terms of executive dysfunction, but as a result of a generalised spatial problem-solving deficit due to the loss of white matter. Anderson et al (2002) identified significant symptoms of executive dysfunction in children with hydrocephalus in both auditive-verbal and visuo-per-ceptual tests.…”
Section: Memorymentioning
confidence: 99%
See 3 more Smart Citations